(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Series of ciprofloxacin derivatives (IVb1 -IVb4) were designed and synthesized by incorporation of thiazole ring (which has an antibacterial activity) and some of its derivatives into the secondary amine of piperazine ring at the C-7 position of ciprofloxacin nucleus. The chemical structures of the synthesized compounds were confirmed by spectral analysis, such as FT-IR and 1HNMR, and some of their physicochemical properties were recorded. An in-vitro study was conducted to evaluate their antibacterial activity by using the agar-well diffusion method (AWD). It was found that the topmost inhibition zone was for the compounds IVb1 and IVb3 against S. aureus and the lowest inhibition zone for compound IIIb against E. coli. In Silico study was performed by Molecular Operating Environment (MOE) program and showed that all the target compounds have an affinity toward topoisomerase enzyme, and these results were consistent with the in vitro study, as the compound IVb3 has the highest docking score value.